Biocompatibility and bone tissue compatibility of alumina ceramics reinforced with carbon nanotubes. (July 2012) - Ogihara, Nobuhide; Usui, Yuki; Aoki, Kaoru; Shimizu, Masayuki; Narita, Nobuyo; Hara, Kazuo; Nakamura, Koichi; Ishigaki, Norio; Takanashi, Seiji; Okamoto, Masanori; Kato, Hiroyuki; Haniu, Hisao; et al.
Aims: The addition of carbon nanotubes (CNTs) remarkably improves the mechanical characteristics of base materials. CNT/alumina ceramic composites are expected to be highly functional biomaterials useful in a variety of medical fields. Biocompatibility and bone tissue compatibility were studied for the application of CNT/alumina composites as biomaterials.Methods & results: Inflammation reactions in response to the composite were as mild as those of alumina ceramic alone in a subcutaneous implantation study. In bone implantation testing, the composite showed good bone tissue compatibility and connected directly to new bone. An in vitro cell attachment test was performed for osteoblasts, chondrocytes, fibroblasts and smooth muscle cells, and CNT/alumina composite showed cell attachment similar to that of alumina ceramic.Discussion & conclusion: Owing to proven good biocompatibility and bone tissue compatibility, the application of CNT/alumina composites as biomaterials that contact bone, such as prostheses in arthroplasty and devices for bone repair, are expected. Original submitted 23 March 2011; Revised submitted 16 November 2011; Published online 8 March 2012